Population genomic insights into variation and evolution of Xanthomonas oryzae pv. oryzae - Midha, Samriti (Sci Rep, 2017)
Xanthomonas oryzae pv. oryzae ( Xoo) is a serious pathogen of rice causing bacterial leaf blight disease. Resistant varieties and breeding programs are being hampered by the emergence of highly virulent strains. Herein we report population based whole genome sequencing and analysis of 100 Xoo strains from India. Phylogenomic analysis revealed the clustering of Xoo strains from India along with other Asian strains, distinct from African and US Xo strains. The Indian Xoo population consists of a major clonal lineage and four minor but highly diverse lineages. Interestingly, the variant alleles, gene clusters and highly pathogenic strains are primarily restricted to minor lineages L-II to L-V and in particularly to lineage L-III. We could also find the association of an expanded CRISPR cassette and a highly variant LPS gene cluster with the dominant lineage. Molecular dating revealed that the major lineage, L-I is youngest and of recent origin compared to remaining minor lineages that seems to have originated much earlier in the past. Further, we were also able to identify core effector genes that may be helpful in efforts towards building durable resistance against this pathogen.